The use of computers in occupational therapy for visual-scanning training. - Ross FL (American Journal of Occupational Therapy, 1992)
This study examined the effect of computer-assisted remediation, with the use of specific visual-scanning software, in the retraining of a functional scanning deficit. Three subjects who displayed significant deficits in visual scanning were selected. A single-subject study was conducted, involving an ABA multiple baseline across-subjects design. Introduction of computer-based intervention with visual-scanning software occurred after 2 or 3 weeks of the gathering of baseline data. Removal of this intervention followed six to nine sessions of 15 to 30 min each over 3 weeks, and data were collected over a 2-week return-to-baseline phase. The dependent variables -- speed, accuracy, and the number of re-referencing glances -- were measured on functional performance of a grocery-shelf scanning task. Analysis with the two standard deviation band method did not reveal a significant change in performance on the functional task between the three phases. Visual and graphic analyses confirmed that computer intervention did not significantly affect performance on the functional task. The clinical significance of the results suggest that software-assisted remediation may not be an appropriate modality for achievement of a functional occupational therapy outcome.